1993
DOI: 10.1159/000171412
|View full text |Cite
|
Sign up to set email alerts
|

Management of Peptic Oesophageal Stricture

Abstract: Peptic oesophageal stricture develops in approximately 10-15% of patients with inadequately treated reflux oesophagitis and poses a difficult clinical problem. The management of reflux oesophagitis has been revolutionised by improvements in medical management, endoscopic and balloon techniques of oesophageal dilatation. The major advance has been the development of inhibitors of gastric acid secretion: histamine receptor antagonists and H+ + K+ + ATPase inhibitors. Studies have recently s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…This physiologic process is separate from GERD, a pathologic process with an incidence of 2% to 7% in children defined as GER associated with complications [9]. These complications may include esophagitis, Barrett esophagus, esophageal stricture, or extraesophageal conditions such as asthma, pneumonia, chronic cough, sleep apnea, and poor dentition and occur with a frequency of 5% to 15% in children with GERD [10,11]. In agreement with other studies, we found a higher incidence of GERD leading to PS in male children; and the majority of our strictures were identified in the lower third of the esophagus [12].…”
Section: Discussionmentioning
confidence: 99%
“…This physiologic process is separate from GERD, a pathologic process with an incidence of 2% to 7% in children defined as GER associated with complications [9]. These complications may include esophagitis, Barrett esophagus, esophageal stricture, or extraesophageal conditions such as asthma, pneumonia, chronic cough, sleep apnea, and poor dentition and occur with a frequency of 5% to 15% in children with GERD [10,11]. In agreement with other studies, we found a higher incidence of GERD leading to PS in male children; and the majority of our strictures were identified in the lower third of the esophagus [12].…”
Section: Discussionmentioning
confidence: 99%